Efektifitas Reinforcement Negatif dalam Meningkatkan Percaya Diri Peserta Didik - Wira Solina; Aida Nurmala Sari; Alfaiz Alfaiz (Jurnal Neo Konseling, 2020)
The background of this research is the students who have lack confidence because  of  themselves  or  their  environment.  The  aim  of  this  research  is: to describe confidence of the students negative reinforcement was given, to describe confidence of the student after negative reinforcement was given and the effectiveness of negative reinforcement to increase confidence of the student. Research design of this research is quasi experimental. The population of this research is 259 students and the sampling is 50 students using purposive sampling. The technique of data analysis is using percentage technique and  t-test  analysis.  The  results of  this research are: (1) confidence of the student before being given negative reinforcement in fairly confidence category, (2) confidence of the students after being given negative reinforcement in fairly confidence category, (3) negative reinforcement is effective in increasing the confidence of the students with the result of t-test is negative reinforcement 2,121. Therefore, effective negative reinforcement methods are applied to the classroom educators to help learners improve their self confidence.